Motivation of the students of the Arabic language department towards the subject of teaching methods and its impact on the achievement of the subject - Mohammed Nareeman Shakir (Zanco Journal of Humanity Sciences, 2023)
This research examines the motivation of students in the Arabic language department and studies the impact on the outcome and achievement in the subject by students, because this study is an analytical study, and the essence of the study wanted to be divided into an introduction and five topics as follows: The first Theme: In this section, we define the terms used in the research's title, as well as the research problem, the significance of its goals, and its constraints. The second Theme: This section is devoted to the theoretical underpinnings of the research as well as studies that have previously focused on issues that are comparable to the one on which this study is centered. The third Theme: This section provides an explanation of the research program and the scope of the research and its example. The fourth Theme: In this section, we have discussed the results of our study. 1-The importance of knowing the students ' opinions about the way they prefer the teacher to teach, which would make the material attractive to the students and understand and assimilate it. 2 - Benefit from the incentive scale to deal with students according to their wishes. 3- Diversification of teaching methods have an effective impact on motivation toward the teaching methods subject, and this is also true of the other subjects taught in the Arabic language department. 4-the research showed that the subject of teaching methods is one of the subjects that accept flexibility and adaptation to new developments, and it is also a link between all the subjects that are taught, it is the core and the basis that cannot be ignored no matter how important other subjects are،No matter how scientifically well-informed the teacher is about the content of his/her subject, it is pointless if she/he does not improve the method that is suitable for students. 5- The fifth Theme: we have included the main conclusions, recommendations, and results in this study: The sample of this study consisted of (92) students of male and females and both sexes were divided into two groups, (13) male students and (79) female students in the Department of Arabic Language / the Third stage This Research also used the correlation factory tool between the Pearson's tests and the Tai and Alpha Kurnbach tests, which was equal to (0.126), which is evidence of the viability of this statistic and its consistency to achieve the objectives of the study.